Assessing students' perceptions of statistics and approaches to learning IT - Bai, Xueni (2008)
This study explores students’ perceptions of Statistics and their approaches to learning it. The study seeks to find out the factors that influence students’ perceptions of Statistics and the factors that influence students’ approaches towards learning Statistics. In addition, the inter-relationship between perceptions and approaches is discussed.